FIGURE 13. A–D, Acanthonyx petiverii H. Milne Edwards, 1834. A, B in Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean ... - In, First Published (Zenodo, 2022)
FIGURE 13. A–D, Acanthonyx petiverii H. Milne Edwards, 1834. A, B, Juvenile male, cl 4.5 mm, cw 2.8 mm (MZUSP 40671). C, D, Ovigerous female, cl 9.5 mm, cw 13 mm (MZUSP 40567). Arrows indicate in (A) the first branchial lobe inconspicuously developed and in (B) the propodi of P2–P5 without the characteristic compressed, dilatated shape. Photographs by A. Pol. ... : Published as part of In, First Published, 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 on page 29, DOI: 10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155 ...